Harpía (Harpia harpyja) construyendo una plataforma en las Yungas Australes del noroeste argentino - Morales, Adriana Marisel; Sánchez, Nadia Mariel; Rodríguez, Ramiro Ezequiel (Nuestras Aves, 2019)
Este artículo no cuenta con un resumen.